Labour-Market Developments at a Time of Heightened Uncertainty. Issue 1 (2nd January 2017) - Dong, Sarah Xue; Manning, Chris
Abstract : These are testing times for labour-market policies in Indonesia. The country faces two major challenges in an unpredictable international and domestic environment: providing people with better, more secure jobs and raising productivity to help raise living standards and reduce poverty. Over the past several months, new global and domestic threats to economic growth have emerged and may hinder progress in jobs and productivity. In the longer term, the government is searching for new strategies to increase productivity, with a focus on supply-side investments in skills and training. In relation to events abroad, uncertainty has increased over the early initiatives taken by the new US president and his nationalist administration, such as the scuttling of the Trans-Pacific Partnership trade deal. At home, likely to be of some significance for economic policy are mass actions that were levelled against Jakarta's governor but de facto also directed against the government. In the medium term, our assessment of the record of the Joko Widodo (Jokowi) government on the labour market is mixed. Over the past two years, growth has been slower than under the previous administration and hence job creation has also been muted. The experience of a handful of countries in Asia suggests that the government might have done more to stimulate economic growth and create jobs. The disappointing performance of manufacturing stands out. Yet inflation has fallen and the slide in the value of international trade—both exports and imports—has reversed in recent months. Improved fiscal management and a generally successful tax amnesty are other pluses. There was also an unexpected but considerable fall in unemployment in 2015–16, according to labour-force statistics. Some policies, such as the new approach to minimum wages, seem to have had beneficial effects for both business and the economy, and Indonesia has done well in some international rankings, such as the World Bank's Ease of Doing Business index. However, the picture for the medium to longer term seems less bright for the labour market. There has been much talk about raising productivity by improving skills through government support for investment in training and apprenticeships, as well as by expanding vocational training along the lines of the German model. Expanding tourism is seen as one solution to the lack of employment for young secondary- and tertiary-educated jobseekers. But we have an impression of policy-making on the run; often, the argument for government intervention has not been made clearly enough. We argue that Indonesia still lacks a coherent, well-thought-out plan to increase jobs and productivity.